(untitled) (Research, Society and Development, 2023)
Isotretinoin is a synthetic isomer of tretinoin, a compound derived from vitamin A and the active substance of the drug Roaccutan®, being the most indicated first-line treatment for patients with severe and resistant acne, despite its proven efficacy, prolonged administration continues to have controversies arising from its potential adverse effects, these being mucocutaneous changes and systemic and teratogenic toxic effects. This work is a descriptive, qualitative and exploratory case report, aiming to report fetal malformations and physical implications in a child exposed to isotretinoin during the gestational period. The project was approved by the Research Ethics Committee under opinion number: 5,816,399. Patient-associated abnormalities include: facial dysmorphism, outer ear abnormalities (microtia), ocular abnormalities (microphthalmia), depression of the nasal bridge, anterior open bite, neuropsychomotor developmental delays, generalized motor delay, persistence of primitive and tonic reflexes, difficulty in carrying out postural and decubitus changes and absence of gait, delay in cervical control, postural reactions, cognition and language, significant impairment of eye-motor coordination. Isotretinoin is a drug with a powerful teratogenic effect, the relationship between the risks and benefits of using this drug must be carefully evaluated, being an absolute contraindication in pregnant women due to the possibility of organic and systemic changes in the fetus, which may present physical, mental, cognitive disabilities and social.